Моделирование электрического поля в системах с тонкими проводящими стержнями при наличии объемного заряда - Резинкина, Марина Михайловна; Резинкин, Олег Лукьянович; Светличная, Елена Евгеньевна; Сосина, Елена Владимировна (НТУ "ХПИ", 2014)
Выполнены расчеты распределений электрического поля (ЭП) в системе, имитирующей приближающийся к земле лидерный канал молнии и молниеотвод. При этом учтено наличие объемного заряда в стримерной зоне лидера и короны вокруг вершины молниеотвода. Обоснована возможность усечения расчетной области так, что она включает в себя молниеотвод и участок земли, на котором он расположен, а также нижнюю часть лидерного канала молнии.

Calculations of electric field (EF) distributions in the systems simulating downward lightning channel near the earth and a lightning-arrester have been performed. At this, presence of space charge in the streamer zone of lightning leader and corona around a lightning-arrester tip has been taking into account. The numerical method of final volumes modified with regard of presence of thin and long conductive objects like rods or wires by usage of logarithmic law of potentials decrease in the radial direction near rods’ axis has been used for EF calculations. Possibility of truncation of calculated area so that it includes a lightning-arrester and the lowest part of the lightning channel has been shown. The numerical experiments made with the help of the described method have shown that presence of a corona zone around the lightning rod tip has no essential influence on distance to a lightning leader, at which conditions of propagation of an ascending leader from lightning rod are fulfilled.
Modeling of an electric field in systems with thin conductive rods at presence of space charge
Keywords: лидерный канал молнии; молниеотвод; идеально поглощающие слои; electric field; lightning-arrester; space charge